EDUKASI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) SEBAGAI PENDETEKSIAN AWAL KANKER PAYUDARA BAGI KARYAWATI DAN MAHASISWI - Dwi Nugraheny; Asih Pujiastuti; Esa Rengganis; Yuliani Indrianingsih; Anton Setiawan H; Redha Okta Silfina (FIP UNIRA MALANG, 2026)
At present, breast cancer is commonly found among women under 50 years old. This situation may occur due to lifestyle changes, limited knowledge about how to care for breast health, and the lack of early detection habits. One of the easiest methods to detect breast cancer symptoms early is SADARI, or Self-Breast Examination. So far, SADARI education has never been conducted at the Institut Teknologi Dirgantara Adisutjipto. Therefore, this community service activity aims to educate female students and staff at Institut Teknologi Dirgantara Adisutjipto about breast cancer using the SADARI method. This education was carried out through health counseling by medical experts experienced in breast cancer, as well as sharing sessions with breast cancer survivors. Based on the pre-test and post-test results, participants’ knowledge improved from an average of 79.97% to 84.89%. Through this SADARI breast cancer education, it is expected that female students and staff at Institut Teknologi Dirgantara Adisutjipto will become more aware, develop early detection habits, and help prevent future risks, thereby improving recovery chances and reducing disease severity.